1982
DOI: 10.1038/clpt.1982.86
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of effects of marihuana cigarettes of three different potencies

Abstract: Marihuana cigarettes containing 1.32%, 1.97%, and 2.54% delta 9-tetrahydrocannabinol (THC) were smoked by six experienced marihuana users at weekly intervals in a double-blind cross-over design under laboratory conditions. Puff duration, number of puffs taken, duration of inhalation holding, interval between puffs, and duration of smoking were recorded for each cigarette smoked. The portion of each cigarette remaining after smoking was weighed and analyzed to determine THC content. Subjective ratings of the "h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
80
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(85 citation statements)
references
References 0 publications
5
80
0
Order By: Relevance
“…Studies using marijuana cigarettes with maximal THC contents ranging from 1.24 to 2.54% did not observe a significant titration of THC intake (e.g., Cappell et al, 1973;Perez-Reyes et al, 1982;Wu et al, 1988;Chait, 1989;Kelly et al, 1994a), while studies which observed a significant titration of THC intake used cigarettes with maximal THC contents ranging from 3.9 to 4.0% (Herning et al, 1986;Nemeth-Coslett et al, 1986). It appears that the ability of subjects to discriminate between different dose levels of THC might affect their marijuana smoking behavior.…”
Section: Self-administration Of Cannabinoids In Human Subjectsmentioning
confidence: 92%
See 2 more Smart Citations
“…Studies using marijuana cigarettes with maximal THC contents ranging from 1.24 to 2.54% did not observe a significant titration of THC intake (e.g., Cappell et al, 1973;Perez-Reyes et al, 1982;Wu et al, 1988;Chait, 1989;Kelly et al, 1994a), while studies which observed a significant titration of THC intake used cigarettes with maximal THC contents ranging from 3.9 to 4.0% (Herning et al, 1986;Nemeth-Coslett et al, 1986). It appears that the ability of subjects to discriminate between different dose levels of THC might affect their marijuana smoking behavior.…”
Section: Self-administration Of Cannabinoids In Human Subjectsmentioning
confidence: 92%
“…During the following quarter century, scientists attempted, mostly with little success, to further demonstrate a THC dose-regulation phenomenon with smoked marijuana (Ashton et al, 1981;Perez-Reyes et al, 1982;Wu et al, 1988;Chait, 1989;Zacny and de Wit, 1991;Kelly et al, 1994a, but see also: Azorlosa et al, 1992;Harder and Rietbrock, 1997;Block et al, 1998). However, Herning and colleagues (1986) observed that experienced marijuana smokers took significantly more puffs with longer intervals between puffs while smoking high potency (3.9% THC) compared to low potency (1.2% THC) marijuana cigarettes and they also inhaled substantially larger (46%) volumes of air.…”
Section: Self-administration Of Cannabinoids In Human Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of clinical studies of marijuana cigarette smoking (Perez-Reyes et al 1982) indicate that, on the average, smokers puff more often (2.6 puffs per minute) than the puff frequency used in the Davis cigarettesmoking study (2 puffs per minute) (Davis et al 1983). Therefore, it is reasonable to assume that when subjects smoke marijuana cigarettes, the amount of THC lost in sidestream smoke is not as large as that found in the cigarette-smoking-machine experiments.…”
Section: Figure 3 Fate Of Thc During Marijuana Cigarette Smokingmentioning
confidence: 99%
“…We have conducted studies in which the number of puffs, the puff duration, the interval between puffs, and the duration of marijuana cigarette smoking of similar or different (Perez-Reyes et al 1982) potencies were measured. However, in these studies, the critically important puff volume parameter was not measured.…”
Section: Smoking Dynamics Marijuana Cigarette Smokingmentioning
confidence: 99%